Lestat de Lioncourt: metáfora do Narciso contemporâneo - Silva, Carla Serafin Ferreira e (2017)
This research aims to reflect on the idealization of immortality in contemporary times. Keeping in mind the dimensions taken by the fear of death in the last centuries and the metaphorical potential of the vampire figure - a recurrent imaginary construction - we will problematize the theme from a theory of narcissism. Supported in the discussions about the presence of narcissistic psychological traits in today's society, our proposal is to discuss the appeal of immortality to a sensibility that extends and leads to other dimensions the meaning of life and survival. We will thus relate the current individual or contemporary Narcissus to the image of the vampire Lestat de Lioncourt, creation of the American writer Anne O'Brien Rice, who we will call Narcissus-vampire in reflections on the fear of death, as a characteristic expression of a society based on extreme individualism, in which Lestat can be seen as an example of the image through which Narcissus falls in love. Thus, our proposal is to understand the contemporary man's fear of his mortality as a typical characteristic of a sensibly narcissistic society, which expresses through the figure of the vampire its intense individuality and inordinate love for the self.